2020
DOI: 10.1039/d0ra03704d
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, characterization and evaluation of a new film based on chitosan, arginine and gold nanoparticle derivatives for wound-healing efficacy

Abstract: It is well-known that the combination of polymers and nanoparticles (NPs) provides optimised wound dressing and accelerates wound healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Multiple studies have reported that the modification of chitosan/arginine/AuNPs improved the hydrophilicity, mechanical strength, and antibacterial properties of the film, which in turn provided an enhanced environment for cell adhesion and proliferation. A cell counting Kit-8 (CCK-8) was used to determine the survival rates [ 59 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…Multiple studies have reported that the modification of chitosan/arginine/AuNPs improved the hydrophilicity, mechanical strength, and antibacterial properties of the film, which in turn provided an enhanced environment for cell adhesion and proliferation. A cell counting Kit-8 (CCK-8) was used to determine the survival rates [ 59 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to our previous work [ 35 ], the l-arginine grafted chitosan (CS-Arg) was prepared by amidation of the primary amine groups present in CS glucosamine (GlcN) units by using EDC/NHS as coupling agents. Briefly, chitosan (0.4 g) was dissolved in 1% acetic acid (20 ml) to form homogeneous aqueous solution at ambient temperature.…”
Section: Methodsmentioning
confidence: 99%
“…The opportunistic microbial contamination and colonization of wounds generally lead to the delayed and circumstantial improper healing process, but it may also lead to severe infections and critical healthcare complications [ 360 , 361 ]. Therefore, impressive attention was oriented on the development of anti-infective wound dressings, which can be produced by embedding dressing materials with different antimicrobial agents, such as synthetic antibiotics [ 362 , 363 ], essential oils [ 364 , 365 ] and antibacterial nanoparticles [ 366 , 367 , 368 ].…”
Section: Silver Nanoparticles For Wound Carementioning
confidence: 99%